TRANSACTIONS: A CELEBRATION OF FIFTY VOLUMES OF STAFFORDSHIRE ARCHAEOLOGY AND HISTORY - Totty, Richard (Staffordshire Archaeological and Historical Society Transactions, 2018)
This note is appearing in the 50th volume of the Transactions of the Staffordshire Archaeological and Historical Society as a celebration of the Society’s achievement in reaching this milestone. It is not meant to be a history of Transactions as such, and even less a history of the Society itself, although it inevitably contains elements of both. Rather, it is a tribute to those members of the Society whose foresight in founding the journal should be recognised, to those later members whose labours have ensured its survival, and finally to those individuals without whom it would have failed, namely the authors of the articles published in it. An analysis of the 270 articles published in Transactions in the first 49 volumes gives an insight into the range of topics covered. There is a very broad coverage reflecting the Society’s title as both archaeological and historical. Almost all the subjects relate to the historic county of Staffordshire, and so include articles relating to those parts of the Black Country moved into the new county of West Midlands in 1974.